Implementation of Automatic Chicken Coop Temperature Controller Using DHT11 Sensor and Servo Motor - Mukminin, Mukminin; Rasiban (Journal Innovations Computer Science, 2025)
This study presents the design, development, and evaluation of an automatic temperature control system for broiler chicken coops using NodeMCU and DHT11 sensors integrated within an Internet of Things (IoT) framework. The system was designed to maintain coop temperature stability automatically, minimizing manual intervention and optimizing environmental conditions for broiler productivity. Using a Research and Development (R&D) approach, the system was constructed with hardware components including NodeMCU ESP8266, DHT11 sensor, servo motor, relay, lamp, and cooling fan, while the software utilized Arduino IDE, Python, and Telegram Bot API for real-time monitoring. The seven-day experimental testing, with thirty readings per day, demonstrated that the system maintained an average temperature of 27.6°C (±0.8°C), achieving 98.5% accuracy compared to manual thermometers, with an average error of 0.65%. The actuators exhibited an average response time of 1.8 seconds, ensuring quick adaptation to environmental changes and preventing heat stress in broilers. The automation reduced manual monitoring time by 80% and inspection frequency by 83%, while lowering energy consumption by approximately 40% through temperature-based device activation. These results confirm that low-cost IoT automation enhances environmental stability, animal welfare, and operational efficiency, aligning with the global trend toward precision livestock farming. Future improvements should focus on integrating multi-node systems, adaptive control algorithms, and humidity regulation to expand scalability, reliability, and sustainability in poultry management.